Pembangunan Tugu Sebagai Simbol Identitas Untuk Meningkatkan Citra Desa Sirnajaya - Muhammad Badru Zaman; Cep Imat Ginanjar; Sheilla Fitria; Muhammad Agus Sholehhudin; Dhea Muhamad Faisal Angriawan; Mochamad Risyad Fauzan; Muhamad Rijki Nurjakiah; Suci Nursania; Tsani Hisni Amala; Moh Ramdani; Alya Rahmawati; Yogi Sugiman; Rafi Miftahul Fauzi; Wida Rahayu; Rakhan Sulaeman DJ; Sendy Kresna Gumilar; Andri Hendriyanto; Muhamad Nizar Fadilah; Hari Muhamad Gifari; Siva Aulia Salsabila; Neng Refi Prayoga; Muhammad Firmasnyah Sofyan; Reza Rizkiansyah (Jurnal PkM MIFTEK, 2026)
The village of Sirnajaya in Cisurupan Subdistrict, Garut Regency, has strong environmental and cultural potential, but lacks a physical symbol that represents the village's identity. The absence of such a marker results in low visual appeal, a lack of orientation points, and a decline in community pride. This community service program aims to solve these problems by constructing a monument as a symbol of the village's identity and a landmark that strengthens the image of the region. The method used is a limited participatory approach involving students and village officials in every stage, from planning, design, budgeting, implementation, to handover of results. The results of the activity show that the monument was successfully built in a strategic location with a design that combines aesthetic and local cultural values. In addition to producing a physical product, this program also encouraged collaboration between students, village officials, craftsmen, and the community, thereby strengthening social solidarity. Obstacles in the form of time constraints and weather conditions were overcome through good coordination and schedule adjustments. Overall, the construction of the monument not only resolved the issue of village identity but also increased collective pride and fostered a spirit of sustainable development.